2021
DOI: 10.1186/s12913-021-06282-x
|View full text |Cite
|
Sign up to set email alerts
|

“… the way we welcome them is how we will lead them to love family planning.”: family planning providers in Rwanda foster compassionate relationships with clients despite workplace challenges

Abstract: Background Rwanda has markedly increased the nation’s contraceptive use in a short period of time, tripling contraceptive prevalence in just 5 years between 2005 and 2010. An integral aspect of family planning programs is the interactions between family planning providers and clients. This study aims to understand the client-provider relationship in the Rwandan family planning program and to also examine barriers to those relationships. Methods Thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…These studies, and our data, raise the question of whether CHV programs exploit the volunteer labor of people living in poverty, disproportionately women, to make the health system function [ 38 , 39 ]. However, the unfair burdens of volunteerism exist alongside evidence, from our study and others, that CHVs perceive great value from their community service [ 31 , 35 , 41 43 ], and express willingness to volunteer under financial strain while perceived or potential benefits outweigh the harms [ 38 , 41 ].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…These studies, and our data, raise the question of whether CHV programs exploit the volunteer labor of people living in poverty, disproportionately women, to make the health system function [ 38 , 39 ]. However, the unfair burdens of volunteerism exist alongside evidence, from our study and others, that CHVs perceive great value from their community service [ 31 , 35 , 41 43 ], and express willingness to volunteer under financial strain while perceived or potential benefits outweigh the harms [ 38 , 41 ].…”
Section: Discussionmentioning
confidence: 89%
“…As in numerous other studies, we found that volunteer work imposed profound financial and time burdens on CHVs [ 23 , 31 , 38 , 39 ], which were exacerbated by also delivering free UPT. A growing body of literature on the experiences of CHVs has raised serious concerns about volunteerism, suggesting that volunteer duties may worsen CHVs’ pre-existing poverty [ 38 ], and contribute to overwhelming work and financial insecurity [ 23 , 31 , 40 43 ]. These studies, and our data, raise the question of whether CHV programs exploit the volunteer labor of people living in poverty, disproportionately women, to make the health system function [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the interpersonal level, providers share accurate information, clarify misguided rumors, and help clients find a method that will work well for them. This is especially important to sustaining contraceptive use among dissatisfied users, as continued counselling helps to prevent discontinuation [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, community visits from government representatives explaining the benefits of family planning may be particularly useful in areas where modern contraceptive prevalence remains low. Further investment in human resources such as nurses and CHWs would also be valuable, to improve accessibility and ensure that every household is reached [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rwanda's family planning program is widely recognized as successful (17)(18)(19)(20)(21)(22)(23)(24)(25). In Rwanda in 2020, 58% of married women used modern contraceptives.…”
Section: Introductionmentioning
confidence: 99%